Penerapan Model Experiential Learning Terhadap Peningkatan Keterampilan Bermain Musik Ansamble Peserta Didik Pada Mata Pelajaran Seni Budaya Dan Prakarya Di Sekolah Dasar - Nugraha, Jaka (Faculty Of Education, 2022)
This study aims to determine the effect of applying the Experiential Learning learning model better on improving students' musical ensemble playing skills compared to improving students' musical ensemble playing skills using conventional learning models. This research is motivated by the problem of the low skills of students playing music ensembles at SD Negeri Cicalengka X. students have little skills in playing musical instruments. Teachers only teach what they are good at without proper preparation for learning and are only dominated by single activities, namely singing, because the learning model is less attractive, learning is still teacher-centered, so that students are less active and lack mastery of skills in the learning process. The type of research used is a quasi-experimental design. Type Non Randomize Control Group Preetest and Posttest Design. The population in this study were all fifth grade students of Cicalengka State Elementary School with the total number of classes being 2 classes, while the samples were V A and V B with 30 students in each class. The data was processed using SPSS, by testing the hypothesis of normality test, homogeneity test, and different test. The results of the study showed that the application of the Experiential Learning learning model could improve the skills of playing music in the ensemble of elementary school students. The improvement of the musical ensemble playing skills of elementary school students who received learning using the Experiential Learning learning model was better than those who received acceptable conventional learning.